2017
DOI: 10.1186/s40965-017-0036-1
|View full text |Cite
|
Sign up to set email alerts
|

The VI-Suite: a set of environmental analysis tools with geospatial data applications

Abstract: Background:The VI-Suite is a free and open-source addon for the 3D content creation application Blender, developed primarily as a tool for the contextual and performative analysis of buildings. Its functionality has grown from simple, static lighting analysis to fully parametric lighting, shadowing, and building energy analyses. It adopts a flexible, mesh geometry based approach to the specification of calculation points and this has made it suitable for certain types of 3D geospatial analyses and data visuali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 30 publications
0
27
0
Order By: Relevance
“…The energy model was developed with the 3D design package Blender and simulated with EnergyPlus . Blender geometry and materiality was converted to the EnergyPlus input format by using the VI‐Suite with an add‐on for the 3D content creation application Blender. The basic Blender geometry model is shown in Figure C.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…The energy model was developed with the 3D design package Blender and simulated with EnergyPlus . Blender geometry and materiality was converted to the EnergyPlus input format by using the VI‐Suite with an add‐on for the 3D content creation application Blender. The basic Blender geometry model is shown in Figure C.…”
Section: Numerical Simulationmentioning
confidence: 99%
“…The most current list of maintained software with CityGML support is the one available at the official CityGML website 4 , and hence it is taken here as the authoritative list for this analysis. A quick inspection of the software revealed that support for ADEs is limited.…”
Section: Overview Of Software Support For Adementioning
confidence: 99%
“…fences and city walls. 4 https://www.citygml.org/software/ 5 https://github.com/tudelft3d/3dfier 6 https://data.overheid.nl/data/dataset/3d-model-denhaag…”
Section: Endnotesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, Nichol et al (2005) [29] used 3D Virtual Reality models to assess the quality of city environment for planning purposes. In addition, a number of open-source and free 3D design and visualisation tools are developed for urban environment planning, modelling and simulations [30,31]. In the continuum of urban planning process, the outcomes of strategic urban planning can be used to develop tools and regulations for statutory urban planning.…”
Section: D City Models In Urban Planningmentioning
confidence: 99%